2022
DOI: 10.1002/lno.12152
|View full text |Cite
|
Sign up to set email alerts
|

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes

Abstract: Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass (Zostera marina) meadows provide essential coastal habitat and are vulnerable to a temperature-sensitive wasting disease caused by the protist Labyrinthula zosterae. We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long-term satellite remote sensing of ocean temperature with fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 60 publications
(95 reference statements)
8
37
0
Order By: Relevance
“…Recently, Groner et al ( 23 ) linked warmer temperatures during the eelgrass growing season to increased prevalence of wasting disease in the San Juan Islands, Washington. Aoki et al ( 27 ) observed similar links between warm thermal anomalies and increased wasting disease prevalence across 23° latitude in the Northeast Pacific. Although experimental studies show that warmer temperatures enhance L. zosterae growth and abundance ( 28 ), we do not yet know how eelgrass microbiomes vary along temperature gradients and with fluctuating disease prevalence in natural meadows.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Recently, Groner et al ( 23 ) linked warmer temperatures during the eelgrass growing season to increased prevalence of wasting disease in the San Juan Islands, Washington. Aoki et al ( 27 ) observed similar links between warm thermal anomalies and increased wasting disease prevalence across 23° latitude in the Northeast Pacific. Although experimental studies show that warmer temperatures enhance L. zosterae growth and abundance ( 28 ), we do not yet know how eelgrass microbiomes vary along temperature gradients and with fluctuating disease prevalence in natural meadows.…”
Section: Introductionmentioning
confidence: 80%
“…Warming is hypothesized to disrupt beneficial microbiomes and their functions within marine habitat forming species, like eelgrass, and may contribute to disease outbreaks (2,6,83). Indeed, warm thermal anomalies are linked to higher prevalence of wasting disease along our latitudinal gradient (27) and at our San Juan Island, WA sites (23). This may result from cumulative or interactive effects of warming on plant or pathogen physiology (59,83,84).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations